PERANCANGAN ENTERPRISE ARCHITECTURE PLANNING (EAP) PADA SEKOLAH MENENGAH ATAS: PERANCANGAN ENTERPRISE ARCHITECTURE PLANNING (EAP) PADA SEKOLAH MENENGAH ATAS - Sarif Hamdani, Yiyi Muhidin; Octapiani, Panka (Jurnal Ilmiah Teknologi Infomasi Terapan, 2022)
Enterprise Architecture Planning is a method used to build an enterprise architecture that is an architectural method oriented to the needs of the enterprise, consisting of a specific architecture, applications and technologies accompanied by an implementation plan against the completed architecture to support business activities to achieve the mission of the organization. Enterprise Architecture (EA) in High Schools (SMA) in order to achieve the continuity of changes that exist in these educational institutions and have a good impact on students in the future, to make high schools (SMA) that can compete in real and virtual terms and find out by using existing corporate architectural planning (EAP) guidelines to produce a blueprint containing data, software, as well as useful technologies as a guide for the improvement and development of system quality to support a business function in high school in the future and the application architecture is created after the architecture is processed by the entity so that the application architecture can run on business processes and the organization data management the application architecture also identifies the business functions supported by the application, the data created updated by the application and its impact to existing applications.